HUMANISASI PENDIDIKAN ISLAM: KONSEP DAN IMPLEMENTASI KURIKULUM BERBASIS CINTA DALAM PEMBELAJARAN PAI UNTUK MEMBENTUK GENERASI BERKARAKTER HUMANIS - Lismijar Lismijar (Yayasan An-Nur Meunara Baro, 2026)
This study aims to examine the concept and implementation of the Love-Based Curriculum in Islamic Religious Education (IRE) as an effort to humanize education in shaping a generation with humanistic character. This study employs a qualitative approach using library research methods through the analysis of various relevant scientific literature, such as journals, books, and educational policy documents. The findings indicate that the Love-Based Curriculum is an educational approach that places the value of compassion (mahabbah/rahmah) at the core of the learning process, integrated into the planning, implementation, and evaluation of instruction. Its implementation in PAI instruction is carried out through humanistic, dialogic, and reflective approaches capable of creating a warm, inclusive, and meaningful learning environment. Values of love including love for God, fellow human beings, the environment, and the homeland have been proven to contribute to shaping students’ characters to be empathetic, tolerant, responsible, and spiritually aware. Thus, the Love-Based Curriculum plays a strategic role in restoring the essence of Islamic education as a process of humanization and serves as an alternative solution to the character crisis in the modern era.